2019
DOI: 10.1016/j.bone.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3D bone marrow adipose tissue model

Abstract: Over the past twenty years, evidence has accumulated that biochemically and spatially defined networks of extracellular matrix, cellular components, and interactions dictate cellular differentiation, proliferation, and function in a variety of tissue and diseases. Modeling in vivo systems in vitro has been undeniably necessary, but when simplified 2D conditions rather than 3D in vitro models are used, the reliability and usefulness of the data derived from these models decreases. Thus, there is a pressing need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 69 publications
3
62
0
Order By: Relevance
“…Second, a subpopulation of distinct BM‐‘regulated’ small adipocytes that are metabolically active and systemically regulated in physiological conditions (Scheller et al , ) may be suppressed by MM. Third, as shown in a 3‐dimensional model of adipocyte‐MM cell interaction, MM cells may use fatty acids in adjacent large adipocytes, causing the large cells to shrink and eventually be eliminated in areas highly involved with MM (Fairfield et al , ), as documented in our work.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Second, a subpopulation of distinct BM‐‘regulated’ small adipocytes that are metabolically active and systemically regulated in physiological conditions (Scheller et al , ) may be suppressed by MM. Third, as shown in a 3‐dimensional model of adipocyte‐MM cell interaction, MM cells may use fatty acids in adjacent large adipocytes, causing the large cells to shrink and eventually be eliminated in areas highly involved with MM (Fairfield et al , ), as documented in our work.…”
Section: Discussionsupporting
confidence: 57%
“…The effects of MM on BM adipocytes remain to be elucidated (Morris & Edwards, 2018). Although adipocytes are evident in interstitial BM and support MM growth in vitro (Trotter et al, 2016;Fairfield et al, 2018), adiponectin, an adipogenic factor, has been shown to induce anti-MM activity and is suppressed in MM (Fowler et al, 2011). Recent studies identified 'regulated' adipocytes that are smaller in size than constitutively present large adipocytes (Scheller et al, 2015), and that function as an endocrine tissue (Cawthorn et al, 2014), suggesting that BM adipocytes are heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro culture of BMAs isolated from MM patients has been shown to support myeloma growth and enhance chemoresistance by activating autophagy through leptin, leading to inhibition of caspase cleavage and apoptosis . We have seen similar results in our lab, and also observed that BMAs shrink when cocultured with MM cells, perhaps indicating lipolysis or some other form of delipidation . Furthermore, adipocytes have been shown to support ovarian cancer cells.…”
Section: Bone Marrow Adipose Tissuesupporting
confidence: 81%
“…). As compared with 2D cultures, general metabolic, DNA replication, ribosome, and proliferation pathways were upregulated in BM adipocytes in this model . Implementation of this silk fibroin scaffold by Reagan and colleagues to study myeloma growth, osteogenesis inhibition, and MM–MSC interaction unveiled myeloma support of endothelial cell assembly into capillary‐like structures and cell adhesion‐mediated drug resistance …”
Section: Bone Cancer Applications Of 3d Bone Modelsmentioning
confidence: 83%
“…As compared with 2D cultures, general metabolic, DNA replication, ribosome, and proliferation pathways were upregulated in BM adipocytes in this model. (87) Implementation of this silk fibroin scaffold by Reagan and colleagues to study myeloma growth, osteogenesis inhibition, and MM-MSC interaction unveiled myeloma support of endothelial cell assembly into capillary-like structures and cell adhesion-mediated drug resistance. (59) Using a 3D Matrigel environment to recapitulate the BM niche, the tumoricidal potential of TEGs (αβT cells engineered to express a defined γδTCR), novel αβT cells engineered to express a defined γδTCR cell receptor (TCR), was examined and compared with a conventional 2D model.…”
Section: Multiple Myelomamentioning
confidence: 99%